Spin in Published Reports of Tinnitus Randomized Controlled Trials: Evidence of Overinterpretation of Results - Velde, Hedwig M.; van Heteren, Jan A. A.; Smit, Adriana L.; Stegeman, Inge (Frontiers in Neurology, 2021)
Background Spin refers to reporting practices that could distort the interpretation and mislead readers by being more optimistic than the results justify, thereby possibly changing the perception of clinicians and influence their decisions. Because of the clinical importance of accurate interpretation of results and the evidence of spin in other research fields, we aim to identify the nature and frequency of spin in published reports of tinnitus RCTs, and to assess possible determinants and effects of spin. Methods We searched PubMed systematically for RCTs with tinnitus related outcomes published from 2015 to 2019. All eligible articles were assessed on actual and potential spin using pre-specified criteria. Results Our search identified 628 studies, of which 87 were eligible for evaluation. 95% of the studies contained actual or potential spin. Actual spin was found mostly in the conclusion of articles, which reflected something else than the reported point estimate (or CI) of the outcome (n = 34, 39%), or which was selectively focused (n = 49, 56%). Linguistic spin (‘trend’, ‘marginally significant’, or ‘tendency towards an effect’) was found in 13% of the studies. We were not able to assess the association between study characteristics and the occurrence of spin due to the low number of trials for some categories of the study characteristics. We found no effect of spin on type of journal (OR -0.13, 95% CI -0.56 – 0.31), journal impact factor (OR 0.17, 95% CI -0.18 – 0.51), or number of citations (OR 1.95, CI -2.74 – 6.65). Conclusion There is a large amount of spin in tinnitus RCTs. Our findings show that there is room for improvement in reporting and interpretation of results. Awareness of different forms of spin must be raised in order to improve research quality and reduce research waste.